2017
DOI: 10.1186/s40199-017-0188-7
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Heqi san on rat model of polycystic ovary syndrome through the PI3K/AKT pathway

Abstract: BackgroundHeqi San, a traditional Chinese medicine (TCM) has been reported to regulate hormone levels in patients with metabolic disease, suggesting a potential clinical application. In the current study, we aimed to elucidate the effect of Heqi San on rat model of polycystic ovary syndrome (PCOS).MethodPCOS model was established in female SD rats. Rats were randomly divided into four groups: the control, untreated PCOS model, Heqi San treated PCOS model (8.1 g/kg) and metformin (MET) treated PCOS model (135 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…However, there was a significant troxerutin-caused ( 300 mg/kg) decline in serum and hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5 ~ 3 mIU/ml [32,33], FSH levels varied from 8mIU/ml to 20mIU/ml [22,34]and testosterone varied from 0.2 to 10 ng/ml [32,[34][35][36][37], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Possession Of Beneficial Effects On Animal Models Of Differesupporting
confidence: 91%
“…However, there was a significant troxerutin-caused ( 300 mg/kg) decline in serum and hypothalamic GnRH. In regard to the serum hormone levels in rats, many previous studies have reported that LH were generally in the range of 1.5 ~ 3 mIU/ml [32,33], FSH levels varied from 8mIU/ml to 20mIU/ml [22,34]and testosterone varied from 0.2 to 10 ng/ml [32,[34][35][36][37], which were approximately consistent with the corresponding results in the present study. Conclusively, troxerutin treatment 300 kg/mg to rats for up to 4 weeks inhibited the hyperactive GnRH/LH system in PCOS rats.…”
Section: Possession Of Beneficial Effects On Animal Models Of Differesupporting
confidence: 91%
“…PI3K/Akt signaling is a major downstream of insulin signaling that mediates the effect of insulin on glucose and lipid metabolism [28][29][30]. Under the condition of PCOS, PI3K/Akt signaling is usually inhibited [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these were associated with the NOD-like receptor signaling pathway, MAPK signaling pathway, IL-17 signaling pathway, TNF signaling pathway, PI3K-Akt signaling pathway, NF-kappa B signaling pathway, AGE-RAGE signaling pathway in diabetic complications, Th17 cell differentiation, Toll-like receptor signaling pathway, and chemokine signaling pathway. Among these, the MAPK signaling pathway [30], PI3K-Akt signaling pathway [31], and Toll-like receptor signaling pathway [32] had been reported to be involved in PCOS previously by performing apoptosis and cell-proliferation related processes.…”
Section: Discussionmentioning
confidence: 99%